Knowledge, attitudes, and perception of air pollution in Ireland - K.I. Quintyne; C. Kelly (Public Health in Practice, 2023)
Aim: Air pollution remains a major global public health challenge; and Ireland is no exception to the human health implications of exposure ambient air pollutants. Accurate and timely information can be critical to mitigate the harmful effects of air pollution. This study aimed to assess the knowledge, perceptions, and attitudes to poor air quality in Ireland to assist stakeholders in developing and implementing effective communication pieces and policies about the management of air pollution. Study design: Cross-sectional population-based cohort. Method: Quantitative data on knowledge, attitudes, and perceptions (KAP) were collected from respondents living across Ireland, and the results were analysed with SPSS (Version 28.0). Results: Among the 1005 respondents included in this study, the mean [SD] age was 46.1 [15.3] years; 53% were female (n = 530); and 66% and 35% of respondents were aware of air pollution and its adverse effects on health at a national and local level respectively (n = 668 and n = 353 respectively). In addition, there were significant relationships between socio-demographic and air pollution awareness. There were correlation between respondent’s age, gender, socio-economic group, and locality in Ireland. Conclusion: This study demonstrates that environmental health literacy around air pollution in critically lacking among respondents. Given that air pollution is an increasingly important global priority, opportunities need to create to improve reach and impact of communication of air quality health risk and mitigation measures.